2012
DOI: 10.1371/journal.pone.0033359
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Diversification Patterns among Vesicomyid Bivalves

Abstract: Vesicomyid bivalves are among the most abundant and diverse symbiotic taxa in chemosynthetic-based ecosystems: more than 100 different vesicomyid species have been described so far. In the present study, we investigated the phylogenetic positioning of recently described vesicomyid species from the Gulf of Guinea and their western Atlantic and Pacific counterparts using mitochondrial DNA sequence data. The maximum-likelihood (ML) tree provided limited support for the recent taxonomic revision of vesicomyids bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…Indeed, because genera were initially poorly defined in Vesicomyidae, recent work has attempted to clarify the taxonomy of the family (see Krylova and Sahling 2010 for review). However the taxonomic and phylogenetic study of this group is still in progress, and the incongruence between clades and named genera is fairly evident from our, as well as from other authors' phylogenies (Peek et al 1997;Goffredi et al 2003;Kojima et al 2004;Decker et al 2012). …”
Section: Host Characterizationmentioning
confidence: 60%
See 2 more Smart Citations
“…Indeed, because genera were initially poorly defined in Vesicomyidae, recent work has attempted to clarify the taxonomy of the family (see Krylova and Sahling 2010 for review). However the taxonomic and phylogenetic study of this group is still in progress, and the incongruence between clades and named genera is fairly evident from our, as well as from other authors' phylogenies (Peek et al 1997;Goffredi et al 2003;Kojima et al 2004;Decker et al 2012). …”
Section: Host Characterizationmentioning
confidence: 60%
“…Genome sequencing of symbionts has emphasized several traits typical of maternallytransmitted bacteria, including genome size reduction coupled with the loss of certain genes (Kim et al 1995;Harada et al 2009;Kuwahara et al 2008;Stewart et al 2008). The systematics and evolution of Pliocardiinae hosts have also been studied but their taxonomy is still under debate as genera are typically found non-monophyletic in phylogenetic reconstructions (Kojima et al 1995;Baco et al 1999;Osborn 2001;Goffredi et al 2003;Kojima et al 2004Kojima et al , 2006Decker et al 2012). Yet, apart from large-sized Pliocardiinae vesicomyids, there are in this subfamily smaller-sized species which have been overlooked, and for which very little data is available, both for hosts and associated symbionts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular studies also revealed synonymous species designations that obscured broad trans-oceanic distributions for several clams (Audzijonyte et al, 2012;Kojima, Fujikura, & Okutani, 2004). Phylogenetic analyses of COI sequences from 51 OTUs suggests a recurrent pattern of speciation, leading from shallow to deep habitats in separate ocean basins (Decker et al, 2012). Although these molecular studies have supported some of the morphology-based assignments to genera, examinations of COI sequences alone do not adequately resolve the deeper phylogenetic nodes that might help to define genera.…”
Section: Introductionmentioning
confidence: 97%
“…It is unsurprising, therefore, that molecular systematic studies of extant species have revealed a number of cryptic species complexes and do not support monophyly of many groups currently treated as genera (Audzijonyte, Krylova, Sahling, & Vrijenhoek, 2012;Decker, Olu, Cunha, & Arnaud-Haond, 2012;Goffredi, Hurtado, Hallam, & Vrijenhoek, 2003;Peek et al, 1997Peek et al, , 2000Vald es et al, 2012;Vrijenhoek, Schutz, Gustafson, & Lutz, 1994). Though molecular traits have generally not been incorporated, recent taxonomic descriptions that included soft anatomical characters have greatly improved the diagnoses of species and genera (Cosel & Olu, 2009;Cosel & Salas, 2001;Krylova & Cosel, 2011;Krylova & Sahling, 2006;Krylova, Sahling, & Janssen, 2010).…”
Section: Introductionmentioning
confidence: 99%